Preparation and characterization of poly(lactic acid)/poly(butylene adipate-co-terepthalate)/clay nanocomposites - Osman, Mohd Junaedy (2011)
Poly(lactic acid) (PLA) is a biodegradable plastic that is brittle. Because of this nature, PLA has a limitation in its usage. The toughness of PLA can be improved by adding plasticizer. In this study, poly(butylenes adipate-co-terepthalate) was added to act as a plasticizer for PLA. The new biodegradable plastic, poly(lactic acid)/poly(butylene adipate-co-terepththalate) (PLA/PBAT), PLA/PBAT/sodium montmorillonite (PLA/PBAT/Na-MMT) and PLA/PBAT/organomodified montmorillonite (PLA/PBAT/OMMT) nanocomposites were prepared by using melt blending technique. This thesis describes the preparation and characterization of PLA/PBAT blends, PLA/PBAT/MMT composites and PLA/PBAT/OMMT nanocomposites. In order to improve the compatibility of polymer and clay, the clay was first modified to become organoclay (OMMT). The organoclays were prepared from sodium montmorillonite (Na-MMT) through cation exchange technique using two types of organic surfactants; octadecyl amine (ODA) and dimethyl dioctadecyl amine bromide (DDOAB). Cloisite 20A (C 20A) commercialize organoclay also used to compare the effect of this organoclay to PLA/PBAT blends. The increase in interlayer spacing of OMMT was characterized using XRay Diffraction (XRD) analysis. The presence of alkylammonium ions in organoclay was also studied by Fourier Transform Infrared (FTIR). Thermal behaviour and amount of surfactant intercalate into the clay galleries of OMMT was study by Thermogravimetric analysis (TGA) and elemental analysis respectively. In studying properties of PLA/PBAT blends, the interaction between these two polymers will affect the tensile and mechanical properties of PLA/PBAT blends. In this study, PBAT acts as a plasticizer of PLA whereas the addition of PBAT decreased the tensile strength and tensile modulus of PLA however increased the elongation at break. The interaction between PLA and PBAT was examined by FTIR. From the dynamic mechanical analysis, PLA and PBAT form immiscible blends as there is two peaks at loss modulus curve represented the Tg for PLA and PBAT. This was supported by SEM observation. Water absorption of sample was found have the same trends as the biodegradation rate of the sample. With greater amounts of PBAT, water absorption and biodegradation rate of the sample increase. Since blending PLA and PBAT will result immiscible blends, OMMT is introduce into PLA/PBAT blends system to improve the compatibility between PLA/PBAT and OMMT. The type of modifier plays a significant role to influence the tensile properties of PLA/PBAT/OMMT nanocomposites. Generally, OMMT with more polar modifier give higher tensile properties of PLA/PBAT/OMMT nanocomposites. This was expected due to the hydrogen bonding between PLA/PBAT blends and the hydroxyl group inside the clay galleries. As a result, shifting for C - O group detected on FTIR spectra. Dynamic mechanical studies revealed the same result as the tensile properties. The addition of OMMT into PLA/PBAT blends increased the thermal degradation as shown in TGA. SEM images show the improvement on continuity and compatibility of PLA/PBAT/OMMT nanocomposites as the reduction of cavity and smoother surface. Transmission electron microscopy (TEM) was used to observe the distribution of OMMT and study the type of nanocomposite formed. The addition of OMMT also enhances the barrier properties in term of water absorption of PLA/PBAT/OMMT nanocomposites, which due to increasing of tortousity. The sample was confirmed as biodegradable as it degraded (loss in weight) after 3 weeks of biodegradable test. The effect of clay loading on tensile properties, mechanical properties, thermal properties, water uptake and biodegradability of PLA/PBAT blends, PLA/PBAT/MMT composites and PLA/PBAT/OMMT nanocomposites were discuss in term of clay loading. The optimum clay loading for PLA/PBAT blends is 1%. The tensile strength and tensile modulus increase until 1 % clay loading and start to decrease with increasing clay loading due to the tactoid structure at high clay loading. The mechanical properties and thermal properties increased with increasing clay content due to the enhancement reinforcing action between clay and polymer and the barrier properties of the clay. The tortuous path created after addition of clay influenced the water uptake and biodegradability of PLA/PBAT/OMMT nanocomposites and PLA/PBAT/MMT composites.